Updating the fatty acid profiles of retail bovine milk in China based on an improved GC-MS method: implications for nutrition - Chen, Meiqing; Wang, Fengen; Wu, Xufang; Si, Boxue; Pan, Junyu; Zheng, Nan; Zhang, Yangdong; Wang, Jiaqi (Frontiers in Nutrition, 2023)
The importance of food components to potential benefits and risks to human health is gradually being consumer awareness. Milk is an important part of the lipid content of the human diet, and there are few detailed reports on the fatty acid (FA) profiles of retail milk. In the study, we developed a gas chromatography–mass spectrometry (GC-MS) method to simultaneously determine 82 FAs, including 11 even-chain saturated FAs, 10 odd-chain saturated FAs, 9 branched-chain saturated FAs, 30 monounsaturated FAs, and 22 polyunsaturated FAs; this was applied to analyze samples (186 samples) of commercially available milk from 22 provinces throughout China and to evaluate the nutritional value of these samples based on FA-related indices. The results showed that the overall composition of milk FAs among the different regions was numerically similar, and minor FAs showed few differences. When considering the retail milk FA composition and dairy fat intake in China, regional variations have a limited impact on FA consumption. Moreover, milk accounts for approximately one-third and <10% of the maximum recommended intake of saturated FAs and trans-FAs in consumer diets, respectively. This study provides an updated report on the composition of FAs and the nutritional value of retail milk across China, which can serve as a reference for producers for future research on regulating milk FAs, for consumers to select milk, and for nutrition departments to formulate relevant nutritional guidance recommendations.